2012
DOI: 10.1371/journal.pone.0048057
|View full text |Cite
|
Sign up to set email alerts
|

DSIR: Assessing the Design of Highly Potent siRNA by Testing a Set of Cancer-Relevant Target Genes

Abstract: Chemically synthesized small interfering RNA (siRNA) is a widespread molecular tool used to knock down genes in mammalian cells. However, designing potent siRNA remains challenging. Among tools predicting siRNA efficacy, very few have been validated on endogenous targets in realistic experimental conditions. We previously described a tool to assist efficient siRNA design (DSIR, Designer of siRNA), which focuses on intrinsic features of the siRNA sequence. Here, we evaluated DSIR’s performance by systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…7). Only a small region (429 bp) of the BIRC5 gene screened, which was too short to be designed and found siRNAs with high knockdown efficiency using existing computer algorithms [37,[42][43]. Screening SURER libraries overcomes the shortcomings of computer design algorithms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7). Only a small region (429 bp) of the BIRC5 gene screened, which was too short to be designed and found siRNAs with high knockdown efficiency using existing computer algorithms [37,[42][43]. Screening SURER libraries overcomes the shortcomings of computer design algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the activity of BIRC clones, three siRNAs were chemically synthesized based on the sequences of clones 2, 38, and 42 (c-2, c-38, c-42) and assayed for knockdown of the endogenous BIRC5 gene in HepG2 cells, and the three designed [37] and synthetic siRNAs (s-1, s-2, s-3) used for comparison. Levels of BIRC5 mRNA and protein were determined in siRNA treated cells 48 h after transfection using RT-qPCR and western blots.…”
Section: Figmentioning
confidence: 99%
“…Thus, these tools take into consideration the context sequences of siRNA and its accessibility to target mRNA. Tools of this type include siDirect [18], DEQOR [19], AsiDesigner [20], DSIR [21], and DEsi [22]. Although the abovementioned RNA design tools have been useful, they are limited to designing single RNA molecules which in turn limits their applications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CK2 inhibition has been shown to have anti-tumor effect in human-glioblastoma xenografts [19,20]. In this study, we used an siRNA targeting the beta subunit of CK2 (CK2β), previously reported to inhibit at least 70% of CK2β activity [21]. Control and therapeutic siRNAs have been modified to allow 125 I radiolabelling on different sites: 3' or 5' end of the sense or antisense strand.…”
Section: Introductionmentioning
confidence: 99%